Pelayanan izin usaha secara one single submission di Aceh Barat - Dista Setyaningsih; Fadhil Ilhamsyah; ikhsan ikhsan; Vellayati Hajad (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2021)
T The article talks about the electronic business license service provided by the One Single Submission (OSS) application, which has been implemented at the West Aceh Regency's Office of Investment and One Stop Integrated Services (DPMPTSP). One Single Submission (OSS) One form of public service implementation that implements E-Government. This paper applied qualitative research methods to investigate the phenomena that occur in electronic services. The study's findings show that licensing services try to use the One Single Submission (OSS) application, as evidenced by several research indicators, including OSS's ease of use, trust in business actors' privacy security, service officers' assistance, the OSS website, and the service's content and appearance. OSS that is comprehensive and simple to comprehend. It may be stated that electronic services implementing OSS have been running properly at the West Aceh Regency Investment and One-Stop Service Office.